ASEAN-India and ASEAN-Korea FTA: Global Trade Analysis Project - Ana Shohibul Manshur Al Ahmad (Economic Journal of Emerging Markets, 2014)
The aim of this research is to investigate the effects of the free trade agreement between ASEAN-India (AIFTA) and ASEAN-Korea (AKFTA). The Computable General Equilibrium (CGE) model was applied in this paper with a Global Trade Analysis Project (GTAP) database version 8. The GTAP simulations results show that AIFTA provides a greater positive impact than the AKFTA for each region. The greater improvement in terms of welfare, GDP, trade and investment is generated under the AIFTA scheme. Implication of this research is required of any reallocation of resources shared by each country heading on sectors which have a comparative advantage.